Argumentative strategies in a thread published by Lula: a technodiscursive analysis on X - Gomes Palacios, Graciela (2024)
This study aimed to verify the use of argumentative strategies in a sample of digital discourse, a thread by Lula on platform X. The corpus selection was based on the notion of small corpora (Moirand, 2020). The analysis revealed relevant argumentative strategies according to the adopted framework: the conceptions of discursive staging (Charaudeau, 2006, 2008, 2009) and controversial discourse (Amossy, 2017). The examination of gesture statements and the relationship between the tweets highlighted relationality (Paveau, 2021).